A history of global consumption : 1500 - 1800 - Baghdiantz McCabe, Ina. (New York : Routledge, Taylor & Francis Group, 2015)
"Examines the history of consumption throughout the early modern period. Takes a chronological and global view to the discussion of evolving consumer practice and culture between 1500 and 1800"--Provided by publisher"--
Includes bibliographical references (pages 270-285) and index.
Keywords: Consumption (Economics) -- History; HISTORY / World; HISTORY / Social History; HISTORY / Modern / General